The “Corsica Channel Cold-Water Coral Province” (Mediterranean Sea) - Angeletti, Lorenzo; Castellan, Giorgio; Montagna, Paolo; Remia, Alessandro; Taviani, Marco (Frontiers in Marine Science, 2020)
Over 25 mounds have been identified in the Corsica Channel (Mediterranean Sea) through multibeam bathymetric mapping at depth of 400-430 m, with dimensions ranging from 70 to 330 m, achieving maximum heights of 25 m. Two such mounds were explored in detail by means of Remotely Operated Vehicle, revealing thick coral growth with a predominance of the branching scleractinian Madrepora oculata as main frame-builder, and subordinate Desmophyllum pertusum. The solitary species Desmophyllum dianthus and Javania cailleti add to the biodiversity here, which accounts for at least 50 macro- and megabenthic species. In consideration of the remarkable surface (ca. 3.4 km2) covered by living corals, their density and healthy appearance, and discontinuity with other major CWC occurrences in the Mediterranean Sea, we propose that this area represents a distinct CWC province in a sector already known for the presence of pre-modern CWC mounds. Noticeably, well-developed contourite drift systems occur in the Corsica Channel, lending support to their strict link with coral establishment at depth. The ecosystemic value of the new CWC province calls for proper conservation measures to ensure their present Good Environmental Status.